2017
DOI: 10.1097/md.0000000000007748
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of early-onset bloodstream infection due to Escherichia coli infection in premature babies

Abstract: In early-onset bacteremia among preterm neonates, Escherichia coli (E. coli) is the main pathogen and can cause a high mortality rate. Thus, the predictive factors of mortality and extended-spectrum β-lactamase (ESBL)-producing E. coli in preterm babies with E. coli early-onset bacteremia were reported.We retrospectively reviewed preterm neonates who had E. coli bacteremia occurring within 3 days after birth between 2004 and 2015. Maternal and perinatal information were collected from their medical records and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Full-text screening excluded an additional 5 articles, providing an evidence base of 87 studies (figure 1). 10–96 The 87 studies included in the qualitative analysis were conducted between 1991 and 2017 in 25 countries, mainly in South Korea (14 studies), Thailand (7), USA (7), Taiwan (7) and Spain (7). Sixty (68.9%) studies were performed in HICs, 26 (29.9%) in LMICs and 1 included both HICs and LMICs 56.…”
Section: Resultsmentioning
confidence: 99%
“…Full-text screening excluded an additional 5 articles, providing an evidence base of 87 studies (figure 1). 10–96 The 87 studies included in the qualitative analysis were conducted between 1991 and 2017 in 25 countries, mainly in South Korea (14 studies), Thailand (7), USA (7), Taiwan (7) and Spain (7). Sixty (68.9%) studies were performed in HICs, 26 (29.9%) in LMICs and 1 included both HICs and LMICs 56.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 404 clinical specimens from patients with community-onset E. coli bacteremia in a medical center in southern Taiwan, Hsieh et al identified only 19 (4.7%) isolates were ESBL producers ( Hsieh et al, 2010 ). For premature babies with E. coli bacteremia, a small study including 27 cases showed five (18.5%) isolates were ESBL producers ( Chen I. L. et al, 2017 ). Additionally, this study found that the level of serum alanine aminotransferase was significantly lower in the ESBL-producing E. coli group than that in the non-ESBL-producing E. coli group ( Chen I. L. et al, 2017 ).…”
Section: Esbl Prevalence Of Specific Pathogensmentioning
confidence: 99%
“…For premature babies with E. coli bacteremia, a small study including 27 cases showed five (18.5%) isolates were ESBL producers ( Chen I. L. et al, 2017 ). Additionally, this study found that the level of serum alanine aminotransferase was significantly lower in the ESBL-producing E. coli group than that in the non-ESBL-producing E. coli group ( Chen I. L. et al, 2017 ).…”
Section: Esbl Prevalence Of Specific Pathogensmentioning
confidence: 99%
“…The prevalence and resistance of bacteria have increased over time due to the use of antibiotics in different countries. As a result, continuous epidemiological monitoring along with frequent local adjustment of susceptibility patterns to antimicrobial agents is essential to establish a rational treatment approach [10] . Objectives: The aim of this study was to evaluate the incidence of sepsis caused by E. coli and its antibiotic resistance pattern as well as to assess the potential risk factors in neonates and maternal characteristics in Shiraz.…”
Section: Introductionmentioning
confidence: 99%